An application of indicators to variables in the public opinion polls by CIEP - Navarro Rodríguez, David O. (2017)
This paper represents an approach in the application of indicators by using the public opinion polls developed by CIEP. Based on the most common observed practices literature, several of them calculated using different variables from the polls applied between April 2013 and April 2016. Most of them facilitate con-clusions of the citizenship perception, complementing the work done by a more disaggregate analysis. For instance, the presence of significant changes in the people’s perception about the social environment and the relative performance of the government (regarding other institutions), between the ending of the Chin-chilla Administration (2010-2014) and the beginning of the Solis Administration (2014-2018).